Remote Controlled Plant Watering System Based on IOT Technology - Vrushali Raj Nathe (Journal of Electronic Design Engineering, 2023)
People should be more willing to adopt modern society and the growth of information and communication technology to maximize the role of technology in both business and the home. The majority of agriculture, including the cultivation of paddy, wheat, and vegetables, occurs in rural areas because there isn't enough technology in urban areas to automate such large-scale grain and vegetable production. Farmers leave other tasks and spend the majority of their time watering crops in the field. It is feasible to monitor and regulate the water process in this essay. This experiment is a special scenario that could help researchers study the optimum control method to conserve water by determining the soil moisture, plant growth, and amount of CO2 present surrounding the plant. With the aid of a LAN connection adaptable algorithm, the water consumption log may be observed in real-time and made available to any user as a distributed remote laboratory. For individuals who have a garden within their home, watering plants might be a chore. This little experiment aims to use a typical TV remote to manage plant watering. To detect the IR signals sent by the remote, an IR sensor is connected to the control unit. The control unit receives this information and uses it to turn on or off the DC water pump as needed. In this project, the control device is a microcontroller from the 8051 series. Because of this, one may quickly water the plant with this small project by simply hitting a few buttons on his TV remote.